A Multivariate Analysis between Renewable Energy, Carbon Emission and Economic Growth: New Evidences from Selected Middle East and North Africa Countries - Maku, Owen Affor; Ikpuri, Promise Oghenevwede (International Journal of Energy Economics and Policy, 2020)
The paper investigated cross-cutting issues relating to renewable energy, carbon-emission and economic growth for a group of 8 MENA countries covering the period 1990-2018. Adopting a modified linear Cobb-Douglas production function, the study adopted the Fully-Modified and the Dynamic OLS estimation technique in examining the aforementioned relationship. Findings from the panel FMOLS and DOLS for the region confirm that a significant relationship exists between CO2 emission and economic growth and that renewable energy consumption triggers a significant effect on economic growth as well. Conversely, the panel of the FMOLS result reveals that while economic growth reacts positively from the effect of CO2 emission, CO2 emission reacts negatively from the effect of renewable energy consumption, as against the positive outcome between renewable energy consumption and CO2 emission as reported by the DOLS. This goes to point out that most economies within this region are yet to uncover best and appropriate policies which can control the regulation of renewable energy prices, that can help take into consideration the stability in economic growth structure and at the same time, mitigate the emission of Greenhouse Gases (GHG). Keywords: Non-renewable resources, Renewable resources, Economic growth, Environment, Pollution JEL Classifications: L72, Q20, O40, R11, Q52 DOI: https://doi.org/10.32479/ijeep.10074